EVALUATION OF SOME PLASTIC WASTES AS ADDITIVES TO REINFORCE HIGH-DENSITY FIBERBOARD (HDF) - Kulce, Tuba; Ates, Saim; Olgun, Cagri (Lukasiewicz Research Network - Poznan Technology Institute, 2021)
The use of plastic wastes in the forest product industry as an additive material is an alternative solution for reducing environmental pollution. In this study, different types of plastic wastes, polyethylene terephthalate (PET), polypropylene (PP), and polystyrene (PS), which have various characteristics and considerable potential as reinforcing materials for wood fibers, were added to high-density fiberboard (HDF) in different mixture ratios (25/75, 50/50, 75/25) with commercial fibers. Changes in some properties of the boards, including density, water absorption, thickness swelling, modulus of elasticity (MOE), bending strength (MOR), and internal bond strength, were determined. It was found that water absorption and thickness swelling ratios were lower in the boards with plastic waste additive than in the control samples. Moreover, the mechanical properties of the samples using plastic waste (except PET) were nearly as good as those of the control samples. The results indicate that PP and PS wastes can be considered for use in the reinforced HDF production process, with different mixture ratios for different usage areas.
Keywords: 8. Economic growth; 15. Life on land; 12. Responsible consumption